DESCRIPTION OF THE CHARACTERISTICS OF PREGNANT WOMEN’S KNOWLEDGE ABOUT BLOOD SUPPLEMENTING TABLETS IN BENGKULU CITY - Tifani, Anisah; Andika, Puteri; Syahnaz, Khariza Fadhila (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Anemia during pregnancy is the most serious stage of iron deficiency, which is characterized by decreased iron reserves, decreased serum iron concentration, low transferrin saturation, and decreased hemoglobin concentration or hematocrit value. The aim of this study was to determine the characteristics of pregnant women, namely age, education level and occupation regarding blood supplement tablets at the Jalan Gedang Health Center, Bengkulu City in 2023. The research design used was cross sectional. The population in this study were pregnant women and recorded in the Jalan Gedang Community Health Center Working Area, Bengkulu City, there were 32 pregnant women while the sample was 24 pregnant women. The research results show that the majority of pregnant women at the Jalan Gedang Community Health Center, Bengkulu City are in the reproductive age category, namely 96%. The majority of pregnant women are highly educated with a percentage of 67%. More than half of pregnant women work. It is necessary to implement and strengthen efforts to increase awareness of pregnant women regarding the importance of consuming blood supplement tablets during pregnancy, appropriate health education and promotion regarding the consumption of blood supplement tablets. The alertness and responsiveness of health workers in detecting problems that could trigger non-compliance with consuming blood supplement tablets by increasing health education for pregnant women about the importance of consuming blood supplement tablets.